Towards robust synchronous belts: influence of surface characteristics on interfacial adhesion. Issue 10 (3rd October 2022) - Bai, Su; Jones, Mitchell P.; Pech de Laclause, Tristan; Jiang, Qixiang; Mautner, Andreas; Swolfs, Yentl; Ho, Kingsley; Knox, Graeme; Bismarck, Alexander
ABSTRACT: The use of carbon fibres is being explored in synchronous belts due to their excellent mechanical properties, chemical and dimensional stability. However, poor adhesion between fibres and the common rubber-fibre adhesive resorcinol-formaldehyde-latex (RFL) compromises load transfer between these constituents. We examined the influence of surface characteristics of commercial glass and carbon fibres, such as fibre surface chemistry, energy and area on carbon fibre-RFL matrix adhesion in model single fibre composites. Fibres with higher surface oxygen content and thus more polar functional groups resulting in a higher surface energy exhibited better adhesion to RFL. Fibre adhesion behaviour to RFL can be ranked using the aspect ratio of the fibre diameter to the critical fragment length as assessed by single fibre fragmentation tests, however, accurate interfacial shear strength values cannot be obtained using the Kelly-Tyson model due to statistical limitations in the treatment of single fibre tensile properties. Our results provide insight into factors affecting fibre-RFL adhesion and identified commercial T700GC-31E carbon fibres as candidates for improved fibre-matrix adhesion for the production of more robust synchronous belts. Graphical Abstract: uf0001